Exploring the Availability and Accessibility of Halal Food Aid in New York City: A Multimethod Study - Hanna Sheikh; Maia Dillane; Lana Khamash; Farah Salam; Dipika Shrestha; Michelle Chau; Nadia Islam; Stella Yi; Perla Chebli (Journal of Nutrition Education and Behavior, 2026)

LGBTQ+ cancer: priority or lip service? A qualitative content analysis of LGBTQ+ considerations in U.S. state, jurisdiction, and tribal comprehensive cancer control plans - Austin R. Waters; Madeline H. Bono; Mayuko Ito Fukunaga; Manal Masud; Megan A. Mullins; Ryan Suk; Meghan C. O’Leary; Swann A. Adams; Renée M. Ferrari; Mary Wangen; Olufeyisayo O. Odebunmi; Sarah H. Nash; et al. (Cancer Causes & Control, 2024)

Correction: Identifying opportunities for collective action around community nutrition programming through participatory systems science - Perla Chebli; Lan N. Đoàn; Rachel L. Thompson; Matthew Chin; Nasim Sabounchi; Victoria Foster; Terry T. K. Huang; Chau Trinh‑Shevrin; Simona C. Kwon; Stella S. Yi (Cancer Causes & Control, 2024)

From study plans to capacity building: a journey towards health equity in cancer survivorship - Prajakta Adsul; Jessica D. Austin; Perla Chebli; Emanuelle M. Dias; Rachel Hirschey; Priyanka Ravi; Aaron T. Seaman; Rosi Vogel (Cancer Causes & Control, 2023)
This article highlights the importance of pausing and reflecting on one's motivation, capacity, and positionality when engaging in health equity research and encourages researchers to engage in critical self-reflection and contribute to the ongoing dialogue on the ethical conduct of health equity-focused cancer research. In response to the urgent need to address health disparities and improve health equity in cancer survivorship care, the Cancer Prevention and Control Research Network (CPCRN) Survivorship workgroup discussed developing a study focused on understanding how racism impacts patient engagement in cancer survivorship care. However, during the study's development, the workgroup recognized limitations in research team composition and infrastructure. The workgroup engaged in critical self-reflections, individually and collectively, leading to the halting of the research study. Consequently, they redirected their efforts towards strengthening the necessary infrastructure for conducting such research, including diverse investigator representation and equitable partnerships with cancer survivors. The description of this process, along with suggestions for reflection, may be helpful and informative to other researchers and research networks seeking to center marginalized voices and work in partnership to address healthcare and health equity.

Identifying opportunities for collective action around community nutrition programming through participatory systems science - Perla Chebli; Lan N. Đoàn; Rachel L. Thompson; Matthew Chin; Nasim Sabounchi; Victoria Foster; Terry T. K. Huang; Chau Trinh-Shevrin; Simona C. Kwon; Stella S. Yi (Cancer Causes & Control, 2023)

Identifying research practices toward achieving health equity principles within the Cancer Prevention and Control Research Network - Prajakta Adsul; Jessica Islam; Perla Chebli; Julie Kranick; Sarah Nash; Hannah Arem; Stephanie Wheeler; Melissa Lopez-Pentecost; Victoria Foster; Rashmi K. Sharma; Tisha Felder; Betsy Risendal; et al. (Cancer Causes & Control, 2023)
Purpose Although there is national recognition for health equity-oriented research, there is limited guidance for researchers to engage partnerships that promote health equity in cancer research. The Cancer Prevention and Control Research Network’s (CPCRN) Health Equity Work Group developed a toolkit to guide researchers in equitable collaborations. Methods The CPCRN’s Health Equity Work Group collectively outlined health and racial equity principles guiding research collaborations with partners that include communities, community-based organizations, implementing partners in the clinical setting including providers and health care organizations, and policy makers. Using a network-wide survey to crowdsource information around ongoing practices, we leveraged and integrated the network’s experience and collaborations. Results Data from the survey formed the preliminary basis for the toolkit, with a focus on sharing fiscal resources with partners, training and capacity building, collaborative decision-making, community-driven research agenda setting, and sustainability. The final toolkit provides reflection considerations for researchers and collated exemplary resources, supported by the contemporary research. Conclusions The toolkit provides a guide to researchers at all experience levels wanting to engage in equitable research collaborations. Future efforts are underway to evaluate whether and how researchers within and outside CPCRN are able to incorporate these principles in research collaborations.

A Culturally Adapted Breast and Cervical Cancer Screening Intervention Among Muslim Women in New York City: Results from the MARHABA Trial - Laura C. Wyatt; Perla Chebli; Shilpa Patel; Gulnahar Alam; Areeg Naeem; Annette E. Maxwell; Victoria H. Raveis; Joseph Ravenell; Simona C. Kwon; Nadia S. Islam (Journal of Cancer Education, 2023)

Principles to operationalize equity in cancer research and health outcomes: lessons learned from the cancer prevention and control research network - Perla Chebli; Prajakta Adsul; Julie Kranick; Catherine L. Rohweder; Betsy C. Risendal; Emily Bilenduke; Rebecca Williams; Stephanie Wheeler; Simona C. Kwon; Chau Trinh-Shevrin (Cancer Causes & Control, 2023)
Reflecting their commitment to advancing health equity, the Cancer Prevention and Control Research Network (CPCRN) established a Health Equity Workgroup to identify and distill guiding principles rooted in health equity, community-engaged participatory research (CBPR), social determinants of health, and racial equity frameworks to guide its collective work. The Health Equity Workgroup utilized a multi-phase, participatory consensus-building approach to: (1) identify recurrent themes in health and racial equity frameworks; (2) capture perspectives on and experiences with health equity research among CPCRN members through an online survey; (3) engage in activities to discuss and refine the guiding principles; and (4) collect case examples of operationalizing equity principles in cancer research. Representatives from all CPCRN centers endorsed nine core principles to guide the Network’s strategic plan: (1) Engage in power-sharing and capacity building with partners; (2) Address community priorities through community engagement and co-creation of research; (3) Explore and address the systems and structural root causes of cancer disparities; (4) Build a system of accountability between research and community partners; (5) Establish transparent relationships with community partners; (6) Prioritize the sustainability of research benefits for community partners; (7) Center racial equity in cancer prevention and control research; (8) Engage in equitable data collection, analysis, interpretation, and dissemination practices; and (9) Integrate knowledge translation, implementation, and dissemination into research plans. Dissemination products, such as toolkits and technical assistance workshops, reflecting these principles will foster knowledge transfer to intentionally integrate health and racial equity principles in cancer prevention and control research.